Communication Skills Health Sciences Studies - Juan Francisco Tejera Concepcion; Miriam Iglesias León; Manuel Cortés Cortés; Gisela Bravo López; Norma Mur Villar; Juan Virgilio López Palacio (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2012)
Background: skills, as cognitive-instrumental components of individuals` performance, have been widely studied in the educational field in order to strengthen the specific teaching of Health Sciences, thus teaching students how to establish an appropriate communication. Objective: to define the communication skills that can be treated through the system of knowledge of the subjects and activities in pre-graduate students majoring in Health Sciences. Methods: at theoretical level: historical-logical, inductive-deductive, analytic-synthetic, systemic, structural, and modeling; at empirical level: documents analysis, meetings with focus groups, observation, surveys to teachers, triangulation of results and expert criteria and at statistical level: percentage analysis and Delphi method. Results: we defined communication skills: for expression, observation and empathetic skills to be developed through a systemic and inclusive character of the course content and practice in pre-graduate studies of Sciences Health. Conclusions: communication skills are essential to the future performance of health professionals. It is necessary that they can be developed in students through the integration among subjects, contents and activities in pre-graduate studies derived from each situation presented in pedagogical and clinical practice.